Sukarno's Visionary Ideas in Formulating Pancasila as The Basis of The State - Kiftiyah, Anif; Septia Wahyuningsih, Ika (Badan Pembinaan Ideologi Pancasila, 2025)
Sukarno's speech at the BPUPK session on June 1, 1945, was a milestone for the founding of the Republic of Indonesia. At that time Sukarno conveyed about the concept of Pancasila, that Pancasila was the thoughts and ideals through a very long process and reflection. This research is a libraryresearch with a qualitative approach and deductive frame of mind. While the analysis in this study uses historical analysis to be able to describe events that occurred in the past about the birth of Pancasila which came from Sukarno's ideas during exile in Ende. The purpose of this research is for the Indonesian people to understand that June 1945 is the creation of Pancasila by going through various phases of struggle and long thoughts from Sukarno's ideas and developing with the thoughts of Indonesian leaders. The finding of this research is that Sukarno tried to unite all the ideas of the founding figures of the nation and groups in formulating Pancasila. Pancasila was born from empirical, philosophical, and juridical formulations so that Pancasila should be used as the basis of the state and ideology of the nation. Although Pancasila was finally established on August 1, 1945, Sukarno declared the spearhead of the idea of ​​Pancasila on June 1, 1945, so that date was also commemorated as the creation of Pancasila in accordance with Presidential Decree no. 24 of 2016 as stated in letters a, b, c, d, e, and f.